Demand, Supply and Utilization of Secondary School Teachers in Kabba/Bunu District of Kogi State,Nigeria - Kayode, Jimoh David (Richtmann Publishing, 2011)
This study examined the demand, supply and utilization of secondary school teachers in Kabba/Bunu LocalGovernment Area, Kogi State. Ten secondary schools were selected from the Local Government (comprising of three schools inurban areas and seven schools in rural areas), using stratified random sampling techniques. Nine teachers were randomlyselected from teachers in senior classes in urban schools and six teachers in rural schools. Relevant data were collectedthrough the use of highly structural and validated questionnaires, titled â€œDemand, Supply and Utilization of Secondary SchoolTeachers (DSUSST)â€ and â€œUtilization of secondary school teachers (USST)â€. The research instrument was administered toselected secondary school principals and subject teachers respectively. The data were analyzed using simple percentage,mean, ratio, Pearson product moment correlation statistics and multiple regression analysis at 0.05 levels of significance. Theresult of the study revealed that there are inadequate basic science and English Language teachers in both rural and urbanschools; there are no incentives for teachers in rural schools and 81 percent of the teachers are qualified. Based on the findings,it is recommended that supply of teachers should be carefully planned and properly executed while meaningful incentives likeleave bonus, free medical treatment for teachers and their families, 15% basic salary as incentives for teachers in difficultterrains should be given to the teachers especially teachers in rural areas.